Potential impact of climate change on resilience and livelihoods in mixed crop-livestock systems in East Africa. Report of a World Bank study - Herrero, Mario; Jones, Peter G.; Karanja, S.; Mutie, Ianetta; Rufino, Mariana C.; Thornton, Philip K. (World Bank, 2013)
Climate-induced livelihood transitions in the agricultural systems of Africa are increasingly likely. A recent study by Jones and Thornton (2009) points to the possibility of such climate-induced livelihood transitions in the mixed crop-livestock rainfed arid-semiarid systems of Africa. These mixed systems cover over one million square kilometers of farmland in West Africa, Eastern Africa, and Southeastern Africa. Their characteristically scant rainfall usually causes crop failure in one out of every six growing seasons and is thus already marginal for crop production. Under many projected climate futures, these systems will become drier and even more marginal for crop production. This will greatly increase the risk of cropping and among the several possible coping and adaptation mechanisms, (e.g. totally abandoning farming, diversification of income-generating activities such as migration and off-farm employment, etc.) agropastoralists may alter the relative emphasis that they currently place on the crop and livestock components of the farming system in favor of livestock